Correlation of HIF-1α, CXCR4 and MMP13 Expression in Laryngeal Squamous Cell Carcinoma with Cervical Nodal Status - Etty Hary Kusumastuti, Etty
Abstract Background: Laryngeal carcinoma is the most common malignancy of the upper respiratory tract, more than 98% are squamous cell carcinoma (SCC). New method is necessary for identifying and αpredicting nodal metastasis in laryngeal SCC. Overproliferating tumor cells will induce hypoxia and release HIF-1α, which in turn will upregulate CXCR4. CXCR4 then will induce MMP13, a protein that degrade extracellular matrix (ECM), thus promoting metastatic process.